A prelude study on influence of hydrophobic ionic liquid on tensile and impact properties of HDPE/KCF biocomposites - Shamsuri, Ahmad Adlie; Md. Jamil, Siti Nurul Ain; Abdan, Khalina (Sciencedomain International, 2021)
In this prelude study, the high-density polyethylene/kenaf core fiber (HDPE/KCF) biocomposites without and containing hydrophobic ionic liquid, namely 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([Emim][NTf2]), were prepared via melt mixing process. The process was carried out by using an internal mixer at 150°C with a rotor speed of 60 rpm. The prepared biocomposites were molded into sheets through compression molding technique at the same temperature. The molded biocomposites were cut into dumbbell and rectangular shapes for tensile and impact tests, respectively. The tensile and impact properties of the biocomposites were determined by using universal testing and impactor machines, correspondingly. The tensile test results indicated that the biocomposites containing [Emim][NTf2] had low tensile stress and tensile modulus. Nevertheless, the biocomposites possessed high tensile extension and impact strength compared to the biocomposite without [Emim][NTf2]. This study deduced that the presence of the hydrophobic ionic liquid like [Emim][NTf2] significantly influenced the tensile and impact properties of the HDPE/KCF biocomposites.